Manipulação discursiva em narrativas conspiratórias no contexto da pandemia de covid-19 - Sousa, Melissa Maria do Nascimento (2024)
This study aims to analyze how conspiratorial narratives published on the website Mídia sem Máscara induce conspiratorial beliefs about the covid-19 pandemic context in their interlocutors. From this main objective, three other specific objectives emerge, namely: i - To describe the discursive manipulation strategies employed in the production of conspiratorial narratives about covid-19 on the Mídia sem Máscara website, considering the construction of global and local meanings; ii - To define the mental representations about covid-19, considering the negative associations made by the website users in relation to the pandemic as a dictatorship and to the exogroup and its criminal, dictatorial, and diabolical actions; iii - To relate the mental representations of those who produce and those who consume the conspiratorial narratives to the social problems resulting from the conspiratorial belief about covid-19, considering the ideological split between the endogroups and exogroups, as well as the anti-vaccine ideology. This research is based on categories and concepts linked to the field of Critical Discourse Analysis, in an approach advocated by Teun A. van Dijk (2005, 2010), whose epistemological framework provided us with anchors for a socio-cognitive treatment of our research object, which is discursive manipulation in conspiratorial narratives on the Mídia sem Máscara website. The methodology was based on documentary research with a qualitative approach and descriptive purposes. Among the results obtained in relation to the rhetorical construction of the conspiratorial narrative analyzed, we found three global meanings or macro-propositions: i - The context of covid-19 has revealed agents of social evil; ii - The health passport is a symbol of the plan to dominate and control the common population; iii - Politicians act above the law by demanding anti-covid-19 protocols; they are persecutors of ordinary citizens. In addition, we observed the performance of subtler microstructures at the level of syntax, the so-called local forms, which we categorized in terms of pronominal relations, active and/or passive voice, nominalizations, enumerations, implicit or explicit comparisons, exemplifications, and inversions. Regarding the analysis of the comments underlying the conspiratorial narrative in question, we observed lexical-semantic structures associated with two major recurring mental representations: Pandemic as a pretext for implementing conspiratorial actions; and negative-other representation: politicians who demand vaccination passports as criminal and dictatorial figures. Finally, we connected the ideological proximities between the editor and the website users, resulting in the following general propositions/beliefs: i: Negative-other representation: politicians who demand vaccination passports as criminal and dictatorial figures; ii: Negative-other representation: taxative ideological polarization of the exogroup; iii: Pandemic as a pretext for implementing conspiratorial actions. These mental representations guide the discourses and attitudes taken by readers in the post-exposure period, generating some social problems such as ideological polarization, social revolt about politics, and the promotion of anti-vaccine ideology, which can lead to the return of diseases that were once eradicated. This panorama shows that issues of language, discourse, and cognition can influence social practices more than one might think, more specifically the success of local and national communities in dealing with public health crises.